Schopenhauer’s Pholosophy Of Pessimism On George Eliot’s Characterization In Silas Marner And The Mill On The Floss - Khelejani, Mostafa Farshbaf (2009)

(untitled)
Arthur Schopenhauer’s pessimistic philosophy presents the world as a dark and evil place where the human being struggles to fulfill the evil and malevolent will’s desires. All human selfish desires, urges, and wants which always cause the individual to struggle painfully, have their roots in this over‐mastering force. Since the evil will is the base of all human worldly attitudes and actions, the individual is destined to face the bitterest miseries in his/her life’s journey. Since Schopenhauer’s pessimism influenced Victorian writers greatly, this textual based research examines and explores how selected characters in both George Eliot’s novels, Silas Marner and The Mill on the Floss, are controlled by the Schopenhauerian omnipresent will. Further, it highlights the portrayal of the weak victims who struggle to fulfill their selfish desires which bring the great misery to every character in return. Silas Marner, George Eliot’s protagonist in Silas Marner, who blindly worshipped God at the Lantern Yard, and then his bright guineas, found no peace and contentment, but rather more suffering and pain with them. Maggie Tulliver, a central character in The Mill on the Floss, made her every effort to satisfy her inner strong need to be praised and loved. Following to fulfill these intense needs, she went through many crises which brought nothing but misery and pain not only to herself but to those around her as well. Although the findings show George Eliot’s created world as a world of evil where the characters are born to suffer, the study also presents the possibility of transition from this dark and unpleasant world to a world where the will is silenced. Realizing how all their efforts were in vain and how their selfish desires brought misery to everyone, the protagonists of both novels reject all their inner will’s worldly needs and desires. Silas Marner finds true peace and contentment by sympathizing with a little, suffering girl who has been ignored by her biological father, while Maggie Tulliver finds it through renouncing all worldly desires and sacrificing herself in order to save others.